Dilemmas of online video review genre: An attempt at describing genre complexity in Polish and German linguistics - Hanus, Anna; Kallaus, Agnieszka (Papers in Linguistics, 2023)
The purpose of the article is to examine the changes in the genre pattern of review resulting from its expansion to a new online communication medium, i.e. the YouTube platform. The case study of two video reviews comprising four levels of analysis (structural, pragmatic, thematic-cognitive and stylistic) aims to compare the canonical version of the arts review and its modern online variants. The authors attempt to determine whether online video film reviews could be regarded as manifestations of the review genre evolution, intermedial adaptation, its genre pattern transformation, or – perhaps – the development of a distinct genre, characteristic of online communication only. Contrastive analysis based on selected methods of Polish linguistic genre studies applied in the context of German text type linguistics is intended to extend the scope of the ongoing research on genre with aspects of Polish and German research perspectives.